Metropolitan Evidence Regarding Small Commercial and Industrial Electricity Consumption - Allen, Keighton R.; Fullerton, Thomas M. (International Journal of Energy Economics and Policy, 2019)
Small commercial and industrial (CIS) electricity demand is an important category of electric energy consumption. Historically, it has received substantially less research attention than residential usage, potentially due to data constraints. This study seeks to partially fill that gap in the energy economics literature by employing a fairly unique data set for the El Paso, Texas, USA metropolitan economy that includes private capital stock estimates from 1978 through2017. The empirical model is specified using a recently developed analytical framework based on duality theory and a derived input demand function. Parameter estimation is completed using an Autoregressive-Distributed Lag model (ARDL) and an Error Correction Model (ECM). In the long-run, CIS customers in El Paso respond only to own-price and the quantity of capital stock per capita. In the short-run, CIS customers adjust their electricity usage in response to changes in all variables except for the price of electricity. The most unexpected result from this analysis is a short-run income elasticity of -0.32, indicating that CIS electricity usage decreases with economic expansion in El Paso, Texas. Keywords: Electricity usage, Metropolitan economic growth, Small commercial and industrial customers, Capital stocks, Duality theory, Derived input demand JEL Classifications: Q41; R11; M21 DOI: https://doi.org/10.32479/ijeep.8233